Philippine medical thesaurus on psychiatry and psychology behavioral discipline and activities and mental disorders in Bikol - Arevalo, Jeremy R.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This mini-thesaurus translated terms from the Psychology and Psychiatry facet of the Medical Subject Headings and used Bikol as the target language. Terms were translated using the top-down approach as a framework of domain analysis, which is based on deductive methods in generating systems. Terms were gathered from existing implementations, the Medical Subject Headings (MeSH) in particular. Terms were then translated using a list of ranked translation tools and supplementary materials. Experts' advices were sought on how the translated terms are written and pronounced. They were also consulted to clarify the meaning of the terms. User surveys were done through informant work. Analysis and methods involved term analysis and lexicographical work.
There were a total of 322 terms that were gathered from the official website of MeSH, 153 Behavioral disciplines and activities terms and 169 Mental disorder terms. Only 124 terms, or 38 percent of the terms translated.
The resultant thesaurus included hierarchical and associative relationships of the terms using such symbols as BT for broader term, NT for narrower term and RT, for related term. Related terms were also gathered from MeSH descriptor data marked as See Also. Equivalent relationships were also used like Used For (UF) and Use. Scope notes or definitions were also provided to most of the terms.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Bicolano -- Medicine; Subject headings, Bicolano -- Psychiatry; Subject headings, Bicolano -- Psychology; Bicolano language -- Medical Bicolano